Policy capacities for mission-oriented innovation policy: A case study of UKRI and the industrial strategy challenge fund - McLaren, Julie; Kattel, Rainer (Technological forecasting & social change, 2025)
A new generation of transformative innovation policies, including a reimagined ‘mission’ approach, centre around tackling societal challenges. Their emphasis on directionality, coordination of different actors and policy mixes goes beyond standard science, technology, and innovation (STI), engaging wider policy and other domains. Whilst missions have become steadily popular and there is growing research on their design, there is much to understand about how such models are implemented in practice. A relative gap in the literature is how science, technology and innovation (STI) organisations develop the policy capacities and capabilities to deliver missions in context. This article provides a case study on how UK Research and Innovation (UKRI) fared whilst implementing the Industrial Strategy Challenge Fund (ISCF). It finds that the policy capacities for missions were not fully present within UKRI and notes several tensions as the organisation worked to develop its capabilities for implementing missions. The paper makes recommendations for how funders can enhance those policy capacities and suggestions for how mission-oriented innovation policy analysis might be developed. •Mission policies are popular but understanding on their implementation is limited.•Policy capacities for missions including navigation, coordination and learning and reflexivity.•Missions require buy-in and a division of labour across a wide range of public actors.•Research and innovation agencies need to develop their policy capacities for delivering missions.